2019
DOI: 10.3389/fimmu.2019.01939
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Anti-PD1 Therapy Following Dendritic Cell Vaccination Improves Survival in a HER2 Mammary Carcinoma Model and Identifies a Critical Role for CD4 T Cells in Mediating the Response

Abstract: Patients with metastatic HER2 breast cancer (MBC) often become resistant to HER 2 targeted therapy and have recurrence of disease. The Panacea trial suggested that HER2 MBC patients were more likely to respond to checkpoint therapy if TIL were present or if tumor expressed PD-L1. We assessed whether type I polarized dendritic cells (DC1) could improve checkpoint therapy in a preclinical model of HER2 + breast cancer. TUBO bearing mice were vaccinated with either MHC class I or class II H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 56 publications
2
36
0
Order By: Relevance
“…A similar finding was demonstrated in a HER2 peptide derived vaccine on a dendritic cell platform that stimulates both CD8+ and CD4+ T cells. This MHC class 2 vaccine was also given in combination with anti-PD-1 therapy and demonstrated improved survival in a preclinical model [30]. It is worth exploring future trials of combinations of check point inhibitors and peptide-based vaccine strategies to improve DFS.…”
Section: Discussionmentioning
confidence: 99%
“…A similar finding was demonstrated in a HER2 peptide derived vaccine on a dendritic cell platform that stimulates both CD8+ and CD4+ T cells. This MHC class 2 vaccine was also given in combination with anti-PD-1 therapy and demonstrated improved survival in a preclinical model [30]. It is worth exploring future trials of combinations of check point inhibitors and peptide-based vaccine strategies to improve DFS.…”
Section: Discussionmentioning
confidence: 99%
“…However, mortality remains high in patients with distant recurrence of the disease after initially successful treatment of early stage breast cancer. Recent advances in immunotherapy of cancer by means of antibody therapies [ 1 , 2 ] and immune checkpoint blockade [ 3 6 ] have prolonged survival of cancer patients, but many patients do not respond to these therapies [ 5 , 7 , 8 ] and those who respond would remain at risk of tumor recurrence [ 6 , 9 , 10 ]. Therefore, a relapse-free cancer cure remains a major challenge for cancer therapeutics.…”
Section: Introductionmentioning
confidence: 99%
“…Although complete remission was not achieved in all mice, we would like to stress the point that tumor burden massively reduced in the combination likely because of inducing a T cell-in amed tumor microenvironment. Other studies reported superior effects when checkpoint-inhibition was given after cessation of the vaccine [38]. Still, the signi cantly prolonged overall survival of MLH1 −/− mice achieved in this study argues in favor of concomitant application.…”
Section: Discussionmentioning
confidence: 50%